Intra-Articular Administration of a Synthetic Lubricin in Canine Stifles - Hayashi, Kei; Bourgeois, Alexandria; Lopez, Daniel; Caserto, Brian G.; Berthelsen, Erin; Krotscheck, Ursula; Reesink, Heidi L.; Kim, Sun Young; Putnam, David (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to evaluate the functional, systemic, synovial and articular changes after intra-articular administration of a synthetic lubricin within healthy canine stifles.Study Design A prospective randomized blinded placebo-controlled study composed of 10 dogs equally divided into either a treatment group (intra-articular synthetic lubricin injection, n = 5) or control group (saline, n = 5). Clinical (orthopaedic examination, gait observation, gait analysis), biochemical (complete blood count and biochemistry profile) and local tissue outcomes (joint fluid analysis, joint capsule and articular cartilage histopathology) were evaluated over a time period of 3 months.Results No significant differences between the treatment group and control group were identified with regard to baseline patient parameters. No clinically significant orthopaedic examination abnormalities, gait abnormalities, biochemical alterations, joint fluid alterations or histopathological alterations were identified over the course of the study.Conclusion The synthetic lubricin studied herein is both biocompatible and safe for a single administration within the canine stifle joint. Further research is necessary to evaluate the clinical efficacy of the synthetic lubricin in canine osteoarthritic joints.
Keywords: osteoarthritis; biocompatibility; dogs; stifle